Terrorism and counterterrorism after the Caliphate - Ellian, Afshin; Rijpkema, Bastiaan; Molier, Gelijn (Eleven International Publishing, 2020)
The Islamic State (ISIS) perplexed the world when its leader Abu Bakr Al-Baghdadi declared a caliphate in 2014. This declaration was not just followed by territorial expansion, but also by several new developments in terrorism's actors, ideology, methods and geopolitics. Terrorism and Counterterrorism after the Caliphate analyzes these new developments in terrorism and counterterrorism in the wake of the ISIS-caliphate. This multidisciplinary volume combines legal, philosophical and international relations perspectives in two main lines of inquiry. First, the concepts relevant to terrorism and counter-terrorism studies are analyzed, such as the status of the 'caliphate', the role of 'ideology' and the links with 'militant democracy'. Second, country-specific contributions discuss the latest developments in terrorism and counterterrorism in Belgium, the Netherlands, Germany, Italy and the United States. Terrorism and Counterterrorism after the Caliphate is essential reading for researchers and policy makers alike, grappling with the postcaliphate world of terrorism. The book constitutes a timely follow-up to earlier volumes in which Leiden Jurisprudence researchers collaborated with other Dutch and international scholars on the issues of terrorism, counter-terrorism and militant democracy: Terrorism: Ideology, Law and Policy (2011), The State of Exception and Militant Democracy in a Time of Terror (2012) and Militant Democracy - Political Science, Law and Philosophy (2018). Afshin Ellian is Professor of Jurisprudence at Leiden University. His latest book is Reflections on Democracy in the European Union (2020, as coeditor). Bastiaan Rijpkema is Associate Professor of Jurisprudence at Leiden University. His most recent book is Militant Democracy: The Limits of Democratic Tolerance (2018). Gelijn Molier is Associate Professor of Jurisprudence at Leiden University. In 2018 he co-edited Strijd om de democratie: essays over democratische zelfverdediging [Struggle for democracy: essays on democratic selfdefense]